Method for preparing bowl-shaped imprinted polymer adsorbent by inducing silicon-based imprinted liquid drops through asymmetric effect and application of bowl-shaped imprinted polymer adsorbent
Drives the silicon-based seal drip-shaped change through asymmetric effects, and adopts the solution-gel method to synthesize the bowl-shaped seal polymer particles, which solves the problem of stability and selectivity in the existing technology. The effect of adsorption and stability of nature and stability.
Patent Information
- Application Number
- CN202411485308.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
In the prior art, when preparing molecularly imprinted polymers, complex preparation processes and harsh reaction conditions make it difficult to guarantee the stability and selectivity of the imprinted sites.
The use of asymmetric effects to induce the transformation of the silicon-based printed liquid droplets, and synthesize the bowl-shaped marks polymer particles through the solution-gel method to achieve high selective adsorption and separation of specific template molecules.
The bowl -shaped seal polymer particles with high selectivity and stability are prepared under gentle and simple conditions, avoiding the impact of complex reaction processes on the stamp assembly, and improving the adsorption and separation effect on template molecules.
Smart Images

Figure CN119346078A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of molecular recognition adsorption and separation functional materials, and specifically relates to a one-step synthesis of bowl-shaped imprinted polymer particle adsorbent by asymmetric force-induced silicon-based imprinted droplets and its separation application. Background Art
[0002] Molecularly imprinted polymers (MIPs) are specific adsorbents prepared by simulating antigen-antibody interaction, also known as "artificial antibodies". Through the polymerization of functional monomers and crosslinkers in the presence of template molecules, specific binding cavities that are complementary to the template in function, size and shape are prepared. The performance of molecularly imprinted polymers is affected by many factors in the preparation process. In addition to the selection of template molecules and functional monomers, crosslinkers also play an important role. Crosslinkers are used to solidify the surrounding space between template molecules and functional monomers to form a highly crosslinked polymer network, and after the template molecules are removed, the recognition ability of the template molecules can still be effectively retained. This requires the selected crosslinker to have good chemical stability, as well as moderate rigidity and flexibility. At the same time, the amount of crosslinker directly affects the crosslinking degree of molecularly imprinted polymers, and then affects the binding force and selectivity between the polymer and the template molecule. When the crosslinking is too low, the formed polymer network will be relatively loose, resulting in poor stability of the imprinted site, which is easily destroyed during the removal of the template molecule. However, when the crosslinking is too high, the formed polymer will have too high rigidity and hydrophobicity, thereby hindering the binding of the template molecule to the imprinted site.
[0003] In recent years, with the increasing variety of silane coupling agents, silicon-based imprinted materials have developed rapidly. The sol-gel method is to hydrolyze and condense silane alkoxy groups (Si(OR)n, R = alkyl, such as Me, Et, Pr, etc.) as molecular precursors to form an inorganic network based on silica. Compared with flexible polymers, silica has a highly cross-linked rigid structure with the potential for high shape selectivity and can form fine imprinting sites. Silica expands very little in the presence of solvents and has excellent thermal stability. These properties also enable it to maintain the shape and size of the imprinted cavity. However, SiO2 particles are often solid spherical particles, which produce fewer molecular imprinting sites. Therefore, the preparation of a carrier material with a large specific surface area is critical to improving the imprinting effect.
[0004] Based on the unique sol-gel process, many studies have shown that the shape of silica can be greatly controlled in the sol stage. There are many methods used to assist the sol-gel method in synthesizing materials with different morphologies, including hydrothermal method, micelle assembly method, phase separation method, etc. However, most of these methods involve complex preparation processes and harsh reaction conditions, such as the use of toxic solvents or strong acids, which will affect or destroy the imprint assembly process. Therefore, it is urgent to develop a simple and gentle means to regulate the morphology of silicon-based imprints. It is common in nature for asymmetric effects to induce deformation of droplets. For example, in the process of water droplets falling, unequal gravity and friction resistance will shape the water droplets into a streamlined shape to reduce air resistance. Similarly, when blowing bubbles, the soap film will also be deformed by a single-direction force. Inspired by this, the present invention designs a gentle, simple and quick means to construct bowl-shaped imprinted composite nanoparticles. Summary of the invention
[0005] The present invention uses 9-vinyl adenine (9-VA) as a functional monomer and β-thymidine (dT) as a template molecule, and forms silicon-based imprinted droplets with hydrolyzed 3-(trimethoxysilyl)propyl methacrylate after pre-assembly. Subsequently, ellipsoidal iron oxide particles are synthesized, and their surfaces are modified with PVP and used as seeds to polymerize with the hydrolyzed silicon-based imprinted droplets under magnetic stirring. Due to the action of centrifugal force, the mass of the iron oxide particles is much greater than the mass of the polymer droplets. Under the action of asymmetric forces, the iron oxide particles will drag the polymer droplets to deform and form a large depression. AIBN is added to initiate polymerization and curing, and composite bowl-shaped imprinted polymer particles containing iron oxide particles are prepared to achieve highly selective adsorption and separation of dT.
[0006] In order to achieve the above technical purpose, the technical solution adopted by the present invention is:
[0007] The present invention provides a method for preparing a bowl-shaped imprinted polymer adsorbent by inducing asymmetric action of silicon-based imprinted droplets, and uses a dT simulation solution to evaluate the performance of the MIP-Fe2O3-MPS adsorbent in selectively adsorbing and separating dT molecules. The method comprises the following steps:
[0008] (1) Preparation of ellipsoidal iron oxide particles (α-Fe2O3)
[0009] First, prepare a sodium hydroxide solution, and slowly drip it into anhydrous ferric chloride solution under strong magnetic stirring. After mixing evenly, add potassium sulfate solution. After stirring evenly, move it to an oven, take it out after reacting for a period of time, wash it with acetone and water, collect it by centrifugation, and put it into a vacuum drying oven to dry it to obtain α-Fe2O3.
[0010] (2) Preparation of PVP-modified α-Fe2O3 particles
[0011] Ultrasonic dispersion of α-Fe2O3 in deionized water, then adding polyvinyl pyrrolidone (PVP) to the dispersion, stirring thoroughly to make the PVP completely dissolved and evenly cover the surface of the iron oxide particles, drying to obtain α-Fe2O3 / PVP particles for later use.
[0012] (3) Preparation of 3-(trimethoxysilyl)propyl methacrylate (MPS) hydrolysis solution
[0013] Place deionized water in a beaker, introduce N2 and then add MPS, and stir at a certain speed until the mixture is dissolved and becomes transparent and uniform to obtain the MPS hydrolysis solution for later use.
[0014] (4) Preparation of pre-assembly solution of template molecules and functional monomers
[0015] An appropriate amount of functional monomer 9-vinyl adenine (9-VA) and template molecule β-thymidine (dT) were weighed and dissolved in deionized water. After nitrogen was introduced, the mixture was assembled at room temperature in the dark to obtain a pre-assembled solution for later use.
[0016] (5) Preparation of bowl-shaped imprinted polymer composite particles (MIP-Fe2O3-MPS)
[0017] The MPS hydrolysis solution and α-Fe2O3 / PVP particles are mixed, stirred at a certain speed to mix evenly, and then an ammonia solution is added dropwise. After the reaction is maintained at a certain speed at room temperature, the pre-assembly solution prepared in step (4) is added, and stirring is continued to fully mix; finally, azobisisobutyronitrile (AIBN) is added and the mixture is placed in an oven for reaction. After the reaction is completed, the particles are graded and centrifuged to remove the secondary nucleated particles. The product after centrifugation is eluted with HCl to remove the template molecule until dT is undetectable in the eluent using a UV-visible spectrophotometer; finally, the purified MIP-Fe2O3-MPS is placed in a vacuum drying oven for drying.
[0018] Similarly, bowl-shaped non-imprinted polymer composite particles (NIP-Fe2O3-MPS) were synthesized in parallel without the addition of dT.
[0019] In step (1), the dosage ratio of the sodium hydroxide solution, the anhydrous ferric chloride solution and the potassium sulfate solution is (5-15) mL: (5-15) mL: 1 mL; wherein the concentration of the sodium hydroxide solution is 5 M, the concentration of the anhydrous ferric chloride solution is 2 M, and the concentration of the potassium sulfate solution is 0.2 M; the reaction temperature is 100° C., and the reaction time is 4-8 days.
[0020] In step (2), the dosage ratio of the α-Fe2O3 ellipsoidal particles and PVP is 1 mg: (0.8-1.2) mg; wherein the molecular weight of PVP is K30;
[0021] In step (3), the ratio of the amount of MPS to deionized water is 1 mL: (15-25) mL; the nitrogen flow time is 30 min; and the stirring speed is 600 rpm.
[0022] In step (4), the ratio of dT, 9-VA and deionized water is 1 mmol: (0.9-1.2) mmol: (40-60) mL. The time of introducing N2 is 30 min, and the time of light-proof assembly is 12 h at room temperature.
[0023] In step (5), the dosage ratio of the α-Fe2O3 / PVP particles, MPS hydrolysis solution, pre-assembly solution, AIBN and ammonia solution is (5-15) mg: (5-15) mL: (8-12) mL: (15-25) mg: 1 mL; wherein the concentration of the ammonia solution is 37% wt.
[0024] In step (5), the stirring speed is 400-1200 rpm;
[0025] In step (5), the reaction time at room temperature is 30 to 40 minutes; the reaction temperature in the oven is 80° C. and the reaction time is 12 hours.
[0026] In step (5), the rotation speed of the graded centrifugal washing is 1000-5000 rpm; the pH of the HCl eluent is 3.0.
[0027] The MIP-Fe2O3-MPS adsorbent prepared by the present invention is used for the selective adsorption and separation of dT.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] With the special characteristics of the sol-gel method, silicon-based imprinted droplets are constructed in the sol stage to ensure the stable assembly of template molecules and functional monomers. The density difference between iron oxide particles and silicon-based imprinted droplets is used to construct asymmetric effects to induce the deformation of silicon-based imprinted droplets. A mild, simple and fast method is proposed to construct bowl-shaped imprinted composite nanoparticles. On the one hand, it avoids the influence and destruction of complex reaction processes and irritating reagents on imprinted assembly, ensuring the integrity of the imprinted site. On the other hand, the simple synthesis steps facilitate further optimization of the effect of cross-linking density on selectivity, achieving highly selective adsorption and separation of dT. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1(a5) is the SEM image of the bowl-shaped imprinted polymer composite particles prepared in Example 1 at a growth time of 30 min; the morphologies of the particles with growth times of (a1) 0 min; (a2) 5 min; (a3) 15 min; and (a4) 25 min are compared.
[0031] Figure 2 This is the TEM image of MIP-Fe2O3-MPS prepared in Example 1.
[0032] Figure 3 The SEM images and contact angles (b1 and b2) of the bowl-shaped imprinted polymer composite particles MIP-Fe2O3-MPS prepared by modifying iron oxide with PVP K30 in Example 1, and the SEM images and contact angles of polymers prepared with other molecular weights of PVP K17 (a1 and a2), PVP K90 (c1 and c2) and PVA403 (d1 and d2) are compared.
[0033] Figure 4 This is the infrared spectrum of MIP-Fe2O3-MPS prepared with different 9-VA dosages in Experimental Example 2.
[0034] Figure 5 These are the single-component adsorption results of dT, AMP, dA, dC, dG and 5-FC by MIP-Fe2O3-MPS and NIP-Fe2O3-MPS prepared in Example 1.
[0035] Figure 6 This is a graph showing the relationship between the adsorption capacity and imprinting factor of MIP-Fe2O3-MPS and NIP-Fe2O3-MPS prepared in Experimental Example 2 and the amount of 9-VA.
[0036] Figure 7 The regeneration capacity of MIP-Fe2O3-MPS and NIP-Fe2O3-MPS in Experimental Example 3 was analyzed through seven consecutive adsorption / desorption cycles. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with specific examples and drawings.
[0038] In the specific implementation of the present invention, the recognition performance evaluation is carried out according to the following method:
[0039] A certain amount of adsorbent was added to 2 mL of PBS solution (pH = 7.4) with a certain initial concentration of β-thymidine (dT). After the adsorbent was in contact with the test solution for 12 hours, the dT solution was passed through a membrane to remove the suspended adsorbent. The concentration of dT in the filtrate was detected by UV-vis spectrophotometer (UV-vis), and the equilibrium adsorption capacity at the corresponding concentration was calculated based on the detection results; a certain amount of adsorbent was added to 2 mL of dT solution with an initial concentration of 300 μmol / L, and the adsorbent was taken out at a certain time gradient, and the adsorption capacity was calculated based on the UV-vis detection results to study the kinetic properties of MIP-Fe2O3-MPS adsorbent. In order to test the selectivity of the adsorbent for extracting dT, several nucleoside compounds with similar structures and properties, such as 2-deoxyadenosine (dA), 2-deoxyguanosine (dG), 2-deoxycytidine (dC), 5-fluorocytidine (5-FC) and adenosine monophosphate (APM), were selected as selective adsorbates to participate in the study of the recognition performance of the adsorbent.
[0040] In order to verify that the adsorbent can still maintain good dT selectivity in complex matrix samples, river water was used as an actual sample for analysis. The actual sample and the spiked sample were prepared in phosphate buffer, and a certain amount of adsorbent was added to 2.0 mL of the actual sample and the spiked sample. After adsorption for 2.0 h, the concentration of each sample in the filtrate was determined by HPLC, and the adsorption capacity was calculated based on the determination results to study the selective recognition and separation ability of MIP-Fe2O3-MPS in complex actual samples.
[0041] The present invention will be further described below in conjunction with specific implementation examples.
[0042] Embodiment 1:
[0043] (1) Preparation of ellipsoidal iron oxide particles (α-Fe2O3)
[0044] First, prepare 100mL of 5M sodium hydroxide solution, and slowly drip it into 100mL of 2M anhydrous ferric chloride solution under strong magnetic stirring. After mixing evenly, add 10mL of 0.2M potassium sulfate solution. After stirring evenly, move it to a 100℃ oven, react for 7 days, take it out, wash it with acetone and water, collect it by centrifugation, and put it into a vacuum drying oven to dry.
[0045] (2) Preparation of PVP-modified α-Fe2O3 particles
[0046] Weigh 100 mg of dried α-Fe2O3 ellipsoidal particles and place them in a 20 mL glass bottle. Add 10 mL of deionized water. After ultrasonic dispersion, add 100 mg of polyvinyl pyrrolidone PVP (K30). Stir well to evenly cover the surface of the iron oxide particles. Dry to obtain α-Fe2O3 / PVP particles for later use.
[0047] (3) Preparation of 3-(trimethoxysilyl)propyl methacrylate (MPS) hydrolysis solution
[0048] Measure 60 mL of deionized water and place it in a beaker. After passing N2 for 30 minutes, add 3 mL of MPS solution and stir at 600 rpm until the mixture is dissolved and becomes transparent and uniform to obtain the MPS hydrolysis solution for later use.
[0049] (4) Preparation of pre-assembly solution of template molecules and functional monomers
[0050] 0.2 mmol of the functional monomer 9-vinyl adenine (9-VA) and 0.2 mmol of the template molecule β-thymidine (dT) were weighed and dissolved in 10 mL of deionized water. After N2 was introduced for 30 min, the mixture was assembled at room temperature in the dark for 12 h.
[0051] (5) Preparation of bowl-shaped imprinted polymer composite particles MIP-Fe2O3-MPS
[0052] Take 10mL of MPS hydrolysis solution and add it to a 100mL flask, add 10mg of α-Fe2O3 / PVP particles, stir and mix at 1000rpm, then add 1mL of ammonia solution (NH3, 37%wt), keep a certain speed and react at room temperature for 30min, then add 10mL of pre-assembly solution and continue stirring for 30min. Finally, add 20mg of azobisisobutyronitrile (AIBN) and place the mixture in an oven at 80℃ to react for 12h. After the reaction is completed, the particles are graded and washed to remove the secondary nucleated particles. The product after centrifugation is eluented with pH=3.0 HCl to remove the template molecule until dT is not detected in the eluent using a UV-visible spectrophotometer. Finally, the purified MIP-Fe2O3-MPS is placed in a vacuum drying oven for drying.
[0053] Similarly, bowl-shaped non-imprinted polymer composite particles NIP-Fe2O3-MPS were synthesized in parallel without the addition of dT.
[0054] Figure 1(a5) is the SEM image of the bowl-shaped imprinted polymer composite nanoparticles MIP-Fe2O3-MPS prepared in Example 1. In addition, the growth of the composite nanoparticles at different growth times is compared: (a1) 0min; (a2) 5min; (a3) 15min; (a4) 25min. First, when the droplets are not in contact with the iron oxide particles, they appear as spherical particles with a particle size of about 200nm. As the silane polycondensation reaction proceeds, the silane droplets on the surface of the iron oxide particles gradually become larger and begin to grow asymmetrically under the action of asymmetric forces. After 15 minutes, the silicon-based imprinted droplets on the single-side surface of the iron oxide are pulled by the asymmetric force to form a cavity, and as the asymmetric force continues to act, the cavity gradually grows away from the iron oxide particles, and finally a bowl-shaped composite nanoparticle with a single-side opening is obtained in 30 minutes.
[0055] Figure 2 This is the TEM image of MIP-Fe2O3-MPS prepared in Example 1, which also confirms the bowl-shaped structure of the material.
[0056] Figure 3 The SEM images and contact angles of the prepared composite nanoparticles after using PVP K30 to modify iron oxide in Example 1, and the SEM images and contact angles of the prepared composite nanoparticles after K17, K90, and PVA403 are compared. Wherein as the K value increases, the molecular weight of PVP gradually increases, the viscosity also gradually increases, and the hydrophobicity also gradually increases. As can be seen from the figure, when the molecular weight is relatively small, the asymmetric force generated is relatively small, and only hollow composite nanoparticles can be obtained, and when the molecular weight is too large, the influence of viscosity gradually dominates, and the iron oxide particles are tightly adhered to the droplets, hindering the occurrence of relative motion, so that bowl-shaped particles cannot be obtained, and due to the large viscosity, many particles are piled up and aggregated. Bowl-shaped composite nanoparticles can be well obtained using K30.
[0057] Example 2
[0058] (1) Preparation of ellipsoidal iron oxide particles (α-Fe2O3)
[0059] First, prepare 50mL of 5M sodium hydroxide solution, and slowly drip it into 50mL of 2M anhydrous ferric chloride solution under strong magnetic stirring. After mixing evenly, add 10mL of 0.2M potassium sulfate solution. After stirring evenly, move it to a 100℃ oven, react for 4 days, take it out, wash it with acetone and water, collect it by centrifugation, and put it into a vacuum drying oven to dry.
[0060] (2) Preparation of PVP-modified α-Fe2O3 particles
[0061] Weigh 100 mg of dried α-Fe2O3 ellipsoidal particles into a 20 mL glass bottle, add 10 mL of deionized water, and after ultrasonic dispersion, add 80 mg of polyvinyl pyrrolidone PVP, stir well to evenly cover the surface of the iron oxide particles. Dry to obtain α-Fe2O3 / PVP particles for later use.
[0062] (3) Preparation of 3-(trimethoxysilyl)propyl methacrylate (MPS) hydrolysis solution
[0063] 45 mL of deionized water was measured and placed in a beaker. After N2 was introduced for 30 min, 3 mL of MPS solution was added and stirred at 600 rpm until the mixture was dissolved and became transparent and uniform to obtain the MPS hydrolysis solution for later use.
[0064] (4) Preparation of pre-assembly solution of template molecules and functional monomers
[0065] 0.18 mmol of the functional monomer 9-vinyl adenine (9-VA) and 0.2 mmol of the template molecule β-thymidine (dT) were weighed and dissolved in 8 mL of deionized water. After N2 was introduced for 30 min, the mixture was assembled at room temperature in the dark for 12 h.
[0066] (5) Preparation of bowl-shaped imprinted polymer composite particles MIP-Fe2O3-MPS
[0067] Take 5mL of MPS hydrolysis solution and add it to a 100mL flask, add 5mg of α-Fe2O3 / PVP particles, stir and mix at 1000rpm, then add 1mL of ammonia solution (NH3, 37%wt), keep a certain speed and react at room temperature for 30min, then add 8mL of pre-assembly solution and continue stirring for 30min. Finally, add 15mg of azobisisobutyronitrile (AIBN) and place the mixture in an oven at 80℃ to react for 12h. After the reaction is completed, the particles are graded and washed to remove the secondary nucleated particles. The product after centrifugation is eluented with HCl at pH=3.0 to remove the template molecule until no dT is detected in the eluent using a UV-visible spectrophotometer. Finally, the purified MIP-Fe2O3-MPS is placed in a vacuum drying oven for drying.
[0068] Similarly, bowl-shaped non-imprinted polymer composite particles NIP-Fe2O3-MPS were synthesized in parallel without the addition of dT.
[0069] Example 3
[0070] (1) Preparation of ellipsoidal iron oxide particles (α-Fe2O3)
[0071] First, prepare 150mL of 5M sodium hydroxide solution, and slowly drip it into 150mL of 2M anhydrous ferric chloride solution under strong magnetic stirring. After mixing evenly, add 10mL of 0.2M potassium sulfate solution. After stirring evenly, move it to a 100℃ oven, react for 8 days, take it out, wash it with acetone and water, collect it by centrifugation, and put it into a vacuum drying oven to dry.
[0072] (2) Preparation of PVP-modified α-Fe2O3 particles
[0073] Weigh 100 mg of dried α-Fe2O3 ellipsoidal particles into a 20 mL glass bottle, add 10 mL of deionized water, and after ultrasonic dispersion, add 120 mg of polyvinyl pyrrolidone PVP, stir well to evenly cover the surface of the iron oxide particles. Dry to obtain α-Fe2O3 / PVP particles for later use.
[0074] (3) Preparation of 3-(trimethoxysilyl)propyl methacrylate (MPS) hydrolysis solution
[0075] Measure 75 mL of deionized water and place it in a beaker. After passing N2 for 30 minutes, add 3 mL of MPS solution and stir at 600 rpm until the mixture is dissolved and becomes transparent and uniform to obtain the MPS hydrolysis solution for later use.
[0076] (4) Preparation of pre-assembly solution of template molecules and functional monomers
[0077] 0.24 mmol of the functional monomer 9-vinyl adenine (9-VA) and 0.2 mmol of the template molecule β-thymidine (dT) were weighed and dissolved in 12 mL of deionized water. After N2 was introduced for 30 min, the mixture was assembled at room temperature in the dark for 12 h.
[0078] (5) Preparation of bowl-shaped imprinted polymer composite particles MIP-Fe2O3-MPS
[0079] Take 15mL of MPS hydrolysis solution and add it to a 100mL flask, add 15mg of PVP-modified α-Fe2O3 ellipsoidal particles, stir and mix at 1000rpm, then add 1mL of ammonia solution (NH3, 37%wt), keep a certain speed and react at room temperature for 30min, then add 12mL of pre-assembly solution and continue stirring for 30min. Finally, add 25mg of azobisisobutyronitrile (AIBN) and place the mixture in an oven at 80℃ to react for 12h. After the reaction is completed, the particles are graded and washed to remove the secondary nucleated particles. The product after centrifugation is eluented with HCl at pH=3.0 to remove the template molecule until no dT is detected in the eluent using a UV-visible spectrophotometer. Finally, the purified MIP-Fe2O3-MPS is placed in a vacuum drying oven for drying.
[0080] Similarly, bowl-shaped non-imprinted polymer composite particles NIP-Fe2O3-MPS were synthesized in parallel without the addition of dT.
[0081] Test Example 1:
[0082] β-thymidine (dT), 2-deoxycytidine (dC), 2-deoxyguanosine (dG), 2'-deoxyadenosine (dA), 5-fluorocytidine (5-FC) and adenosine monophosphate (AMP) were selected as selective adsorbents, and solutions of the above six compounds were prepared with a concentration of 300 μmol / L. 5 mL was taken and added to centrifuge tubes respectively. After shaking at room temperature for 12.0 hours, the adsorbent was collected by centrifugation. Then, the concentration of the compound in the filtrate was determined by ultraviolet-visible spectroscopy (UV-vis), and the adsorption capacity was calculated and obtained based on the results. Figure 5 . It can be found that the adsorption capacity (70.79 μmol / g) of MIP-Fe2O3-MPS and NIP-Fe2O3-MPS obtained in Example 1 for the template molecule dT is significantly higher than that of the other five competitors. That is, the specific adsorption and recognition effect of MIP-Fe2O3-MPS is in the order of dT>dC>dG>5-FC>AMP>dA. Although they have similar molecular structures and functional groups to dT, the adsorption capacity and selectivity of MIP-Fe2O3-MPS for competitors are still much lower than dT because their shape and size do not match the imprinted cavity size. This shows that molecular imprinting technology plays a very important role in improving the selective recognition ability of the adsorbent, and MIP-Fe2O3-MPS has a good selective recognition ability for dT.
[0083] Test Example 2:
[0084] 0.1, 0.2, 0.3, 0.4, and 0.6 mmol of 9-VA were added respectively, and the ratio of the template molecule to the functional monomer was maintained unchanged to change the ratio of the functional monomer to the cross-linking agent MPS in the reaction system, and a series of bowl-shaped imprinted composite nanoparticles were prepared.
[0085] Under the same conditions, bowl-shaped non-imprinted composite nanoparticles were prepared without adding template molecules.
[0086] Figure 4 The chemical functional groups on the surface of MIP-Fe2O3-MPS were studied by Fourier-infrared spectroscopy. The addition of different amounts of functional monomer 9-VA was compared. As the amount of modified 9-VA increased, the stretching vibration peak intensity of OH gradually increased, confirming that MIPs successfully grew into Fe2O3-MPS.
[0087] Take 5mL of 300μmol / L β-thymidine dT in PBS (pH=7.4) and add it to a centrifuge tube. Add 5mg of the adsorbent prepared in Example 1. After the adsorbent is in contact with the test solution for 12.0h, pass the dT solution through a membrane to remove the suspended adsorbent. Use UV-vis to detect the concentration of dT in the filtrate. Calculate the adsorption capacity and imprinting factor based on the results to obtain Figure 6 As can be seen from the figure, the adsorption amount increases with the increase of the amount of functional monomer 9-VA. However, with the increase of the amount of 9-VA added, the imprinting factor shows a trend of first increasing and then decreasing. When 0.3mmol 9-VA is added, the imprinting factor reaches 3.85. When the addition amount of 9-VA increases to 0.4mmol, the imprinting factor begins to decrease.
[0088] Test Example 3:
[0089] For the regeneration of the adsorbent, seven cycles of adsorption / desorption experiments were conducted on the MIP-Fe2O3-MPS and NIP-Fe2O3-MPS obtained in Example 1. 2.0 mg of MIP-Fe2O3-MPS was added to a centrifuge tube containing 2.0 mL of PBS solution (pH = 7.4) with a dT concentration of 300 μmol / L. After 12.0 h of oscillation, the concentration of dT in the solution was detected, and the adsorption capacity Q was calculated. e (μmol / g). After each adsorption, the adsorbed MIP-Fe2O3-MPS was eluted with a pH=3.0 HCl solution at room temperature for 12.0 h. The regenerated adsorbent was then washed with deionized water to neutrality and used for the next adsorption / desorption cycle after drying. Figure 7 As shown, in the first three cycles, the adsorption amount and imprinting factor did not show a significant decrease. After seven cycles, the adsorption capacity of MIP-Fe2O3-MPS for dT decreased from the initial 46.515μmol / g to 40.368μmol / g, and it could still maintain 87% of the initial adsorption capacity, while the imprinting factor did not show a significant decrease, indicating that the sites of MIP-Fe2O3-MPS are relatively stable and have good reusability.
Claims
1. A method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action-induced silicon-based imprinted droplets, characterized in that: The steps include: (1) Preparation of ellipsoidal iron oxide particles α-Fe2O3 First, prepare a sodium hydroxide solution, slowly drip it into anhydrous ferric chloride solution under strong magnetic stirring, add potassium sulfate solution after mixing evenly, move it into an oven after stirring evenly, take it out after reacting for a period of time, wash it with acetone and water, collect it by centrifugation and put it into a vacuum drying oven to dry, and obtain α-Fe2O3; (2) Preparation of PVP-modified α-Fe2O3 particles Ultrasonic dispersion of α-Fe2O3 in deionized water, then adding polyvinyl pyrrolidone (PVP) to the dispersion, stirring thoroughly to make the PVP completely dissolved and evenly cover the surface of the iron oxide particles, drying to obtain α-Fe2O3 / PVP particles for later use; (3) Preparation of 3-(trimethoxysilyl)propyl methacrylate MPS hydrolysis solution Place deionized water in a beaker, add MPS after passing N2, and stir at a certain speed until the mixture is dissolved and becomes transparent and uniform to obtain MPS hydrolysis solution for later use; (4) Preparation of pre-assembly solution of template molecules and functional monomers Weigh an appropriate amount of functional monomer 9-vinyl adenine 9-VA and template molecule β-thymidine dT, dissolve them in deionized water, introduce N2, assemble at room temperature in the dark, and obtain a pre-assembly solution for standby use; (5) Preparation of bowl-shaped imprinted polymer composite particles (MIP-Fe2O3-MPS) The MPS hydrolysis solution and α-Fe2O3 / PVP particles are mixed, stirred at a certain speed to mix evenly, and then an ammonia solution is added dropwise. After the reaction is maintained at a certain speed at room temperature, the pre-assembly solution prepared in step (4) is added, and stirring is continued to be fully mixed; finally, azobisisobutyronitrile AIBN is added and the mixture is placed in an oven for reaction. After the reaction is completed, the particles are graded and centrifuged to remove the secondary nucleation particles. The product after centrifugation is washed with HCl eluent to remove the template molecule until dT is no longer detected in the eluent using a UV-visible spectrophotometer; finally, the purified MIP-Fe2O3-MPS is placed in a vacuum drying oven for drying.
2. The method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action induced silicon-based imprinted droplets according to claim 1, characterized in that: In step (1), the dosage ratio of the sodium hydroxide solution, the anhydrous ferric chloride solution and the potassium sulfate solution is (5-15) mL: (5-15) mL: 1 mL; wherein the concentration of the sodium hydroxide solution is 5 M, the concentration of the anhydrous ferric chloride solution is 2 M, and the concentration of the potassium sulfate solution is 0.2 M; the reaction temperature is 100° C., and the reaction time is 4-8 days.
3. The method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action induced silicon-based imprinted droplets as claimed in claim 1, characterized in that: In step (2), the usage ratio of the α-Fe2O3 ellipsoidal particles and PVP is 1 mg:(0.8-1.2) mg; wherein the molecular weight of PVP is K30.
4. The method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action induced silicon-based imprinted droplets as claimed in claim 1, characterized in that: In step (3), the ratio of MPS to deionized water is 1 mL: (15-25) mL; the nitrogen flow time is 30 min; and the stirring speed is 600 rpm.
5. The method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action induced silicon-based imprinted droplets as claimed in claim 1, characterized in that: In step (4), the dosage ratio of dT, 9-VA and deionized water is 1 mmol: (0.9-1.2) mmol: (40-60) mL; the time of passing N2 is 30 min; and the time of light-proof assembly at room temperature is 12 h.
6. The method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action induced silicon-based imprinted droplets as claimed in claim 1, characterized in that: In step (5), the dosage ratio of the α-Fe2O3 / PVP particles, MPS hydrolysis solution, pre-assembly solution, AIBN and ammonia solution is (5-15) mg: (5-15) mL: (8-12) mL: (15-25) mg: 1 mL; wherein the concentration of the ammonia solution is 37% wt.
7. The method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action induced silicon-based imprinted droplets as claimed in claim 1, characterized in that: In step (5), the stirring speed is 400-1200 rpm.
8. The method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action induced silicon-based imprinted droplets as claimed in claim 1, characterized in that: In step (5), the reaction time at room temperature is 30 to 40 minutes; the reaction temperature in the oven is 80° C. and the reaction time is 12 hours.
9. The method for preparing bowl-shaped imprinted polymer adsorbent by asymmetric action induced silicon-based imprinted droplets as claimed in claim 1, characterized in that: In step (5), the rotation speed of the graded centrifugal washing is 1000-5000 rpm, and the pH of the HCl eluent is 3.
0.
10. Use of the MIP-Fe2O3-MPS adsorbent prepared by the method according to any one of claims 1 to 9 for selective adsorption and separation of dT.
Citation Information
Patent Citations
Core-shell type magnetic surface imprinting nanometer composite material preparation method
CN103601847A
Method for preparing magnetic molecularly-imprinted adsorbent
CN104479072A
Tetracycline molecularly imprinted material and preparation method thereof
CN109721761A
Preparation method of molecularly imprinted magnetic nano material and application of molecularly imprinted magnetic nano material in purification of [gamma]-aminobutyric acid
CN111085011A
Core-shell type magnetic molecularly imprinted polymer material, preparation method and application
CN116328742A